Gonadal dysgenesis in a patient with an X;3 translocation: case report and review. Issue 3 (June 1980) - Carpenter, N J; Say, B; Browning, D
Abstract : A patient with primary amenorrhoea and absence of secondary sex characteristics was found to have a balanced X;3 translocation. This phenotype is reported in approximately one-third of the balanced X;autosome translocation cases. The normal X chromosome is inactive in the present case which is in agreement with most of the similar cases. A review of the 66 balanced X;autosome translocations reported to date is presented.